A cadaver study of mastoidectomy using an image‐guided human–robot collaborative control system. Issue 5 (25th September 2017) - Yoo, Myung Hoon; Lee, Hwan Seo; Yang, Chan Joo; Lee, Seung Hwan; Lim, Hoon; Lee, Seongpung; Yi, Byung‐Ju; Chung, Jong Woo
Abstract : Objective: Surgical precision would be better achieved with the development of an anatomical monitoring and controlling robot system than by traditional surgery techniques alone. We evaluated the feasibility of robot‐assisted mastoidectomy in terms of duration, precision, and safety. Study Design: Human cadaveric study. Materials and Methods: We developed a multi‐degree‐of‐freedom robot system for a surgical drill with a balancing arm. The drill system is manipulated by the surgeon, the motion of the drill burr is monitored by the image‐guided system, and the brake is controlled by the robotic system. The system also includes an alarm as well as the brake to help avoid unexpected damage to vital structures. Experimental mastoidectomy was performed in 11 temporal bones of six cadavers. Parameters including duration and safety were assessed, as well as intraoperative damage, which was judged via pre‐ and post‐operative computed tomography. Results: The duration of mastoidectomy in our study was comparable with that required for chronic otitis media patients. Although minor damage, such as dura exposure without tearing, was noted, no critical damage to the facial nerve or other important structures was observed. When the brake system was set to 1 mm from the facial nerve, the postoperative average bone thicknesses of the facial nerve was 1.39, 1.41, 1.22, 1.41, and 1.55 mm in the lateral, posterior pyramidal and anterior, lateral, and posterior mastoid portions, respectively. Conclusion: Mastoidectomy can be successfully performed using our robot‐assisted system while maintaining a pre‐set limit of 1 mm in most cases. This system may thus be useful for more inexperienced surgeons. Level of Evidence: NA.